1997
DOI: 10.1007/bf02688611
|View full text |Cite
|
Sign up to set email alerts
|

An event-related brain potential investigation of PTSD and PTSD symptoms in abused children

Abstract: We tested 186 children ranging in age from 6 years, 10 months to 13 years, 7 months; 174 suffered either physical and/or sexual abuse, and 12 were nonabused children. Abused subjects were grouped in four different ways. The primary grouping was based on whether subjects satisfied the DSM III-R criteria for posttraumatic stress disorder (PTSD). Secondary groupings were based upon the three symptom clusters used to make the PTSD diagnosis (arousal, avoidance, and reexperiencing). In each of these groupings three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
3
14
1
Order By: Relevance
“…Rather, male veterans with PTSD had significantly steeper P2 amplitude intensity slopes, much like those reported in our previous study of female Vietnam nurse veterans [11] and in the study of abused children with PTSD [10]. These findings suggest that the observed heightened intensity dependence in PTSD is not sex, age, or trauma specific.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Rather, male veterans with PTSD had significantly steeper P2 amplitude intensity slopes, much like those reported in our previous study of female Vietnam nurse veterans [11] and in the study of abused children with PTSD [10]. These findings suggest that the observed heightened intensity dependence in PTSD is not sex, age, or trauma specific.…”
Section: Discussionsupporting
confidence: 81%
“…Contrary to findings of decreased P2 amplitude intensity slopes reported in previous studies of male combat veterans with PTSD [1,9], we found increased P2 amplitude intensity slopes, similar to those reported for female veterans [11] and abused children [10] with PTSD. Additionally, mixed-model, random-effects analysis including the combat-unexposed twins revealed a significant diagnosis × combat exposure interaction.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations